Penerapan Perilaku K3 Pada Dapur Departemen Di Theme Park Dan Resort Pantai Cermin Kec. Perbaungan Kabupaten Serdang Bedagai - Hasriyani, Enny (Tourism, Hospitality And Culture Insights Journal, 2025)
The existence of K3 is an effort to control the course of work activities. However, the occurrence of work safety incidents in a company or institution shows that there are problems occurring in the implementation process. This then becomes a challenge for the company to improve the quality of K3 for employees to work optimally. This also happened in the Kitchen department at the Pantai Cermin Themepark and Resort, Deli Serdang district. This research was conducted in the Kitchen Themepark and Resort Pantai Cermin department, Deli Serdang district using descriptive qualitative research types. So, to find out the extent of the influence of K3 so far on employees, the research tries to examine how K3 behavior is implemented in the Kitchen department at the Pantai Cermin Themepark and Resort, Deli Serdang district. From the results of the research carried out, it turns out that we have not been able to implement K3 behavior well. In fact, the K3 program currently being created has not been able to have an impact on the smooth running of employee activities due to several problems such as communication and lack of control. So this then proves that the readiness of company management in carrying out K3 has not adapted optimally. Research results show that work accidents until August 2024 are still higher than the previous year. Therefore, the Kitchen department at the Pantai Cermin Themepark and Resort in Deli Serdang district must make improvements to the program policies that are currently in effect, and be supported by several management procedures that support the smooth running of employee safety activities.